The Factors That Affect the Adherence of Hypertension Elderly Diet with the Transcultural Nursing Theory Approach - Has, Eka Mishbahatul M; Nugraha, Yanuar Aga; Wahyuni, Erna Dwi (International Journal of Psychosocial Rehabilitation, 2020)
Hypertension is a disease that not controlled can cause heart disease. Based on the results of studies conducted at health services in Mataram, 12 out of 20 elderly suffer from hypertension, and 4 of them have been given a low salt diet, but they are not compliant in carrying out the food. This study aims to analyze the factors that influence adherence to the menu of the elderly with hypertension. This study used a correlational method with a cross-sectional approach. The sampling used purposive sampling and obtained 52 elderly. The independent variables in this study are the level of education, economic factors, family support, culture, and lifestyle. The dependent variable is adherence to the elderly diet with hypertension. The data were collected using a questionnaire and analyzed with Spearman Rho test with a significance level of 0.05. The test results of this study show that there is a relationship between economic factors (p=0.000), family support (p=0.000), culture, and lifestyle (p=0.000) with adherence to an elderly diet with hypertension. Economic factors, family support, culture, and lifestyle are factors that influence adherence to the menu of the elderly with hypertension. So the elderly are expected to maintain dietary compliance by involving family diets and healthy lifestyles to control blood pressure.